Women Friendly Mosque in Banda Aceh: A Study of the Concept of Gender Justice and Gender Planning Perspective - Ismar Ramadani; Siti Nur Zalikha; Faradilla Fadlia (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2021)
All public spaces, including mosques, should be accessible to everyone and must accommodate the needs of all gender groups. This paper analyzes several mosques in Aceh which are considered unfriendly to one gender and several mosques which are considered gender responsive and their impact on the convenience of women to worship in the mosque. This study used a qualitative method with in-depth interviews and gender planning theory as an analytical tool. This study found several findings. First, the female and male congregations experience comfort and discomfort related to spatial planning and facilities. Second, spatial planning and facilities have discriminated against one gender group. Third, mosques in Aceh are generally reserved for men. This resulted in the layout of the mosque not accommodating the needs of women. Therefore, this study recommends that all public spaces, especially mosques, must be designed as gender-friendly buildings, accommodating all needs for worship for both men and women, parents and children, without reducing the value and spatial aspects of the mosque building.